A Lead Iodide Perovskite Based on a Large Organic Cation for Solar Cell Applications. (29th June 2018) - Ma, Chunqing; Shen, Dong; Lo, Ming‐Fai; Lee, Chun‐Sing
Abstract: Methylammonium (CH3 NH3 + ) and formamidinium ((NH2 )2 CH + ) based lead iodide perovskites are currently the two commonly used organic–inorganic lead iodide perovskites. There are still no alternative organic cations that can produce perovskites with band gaps spanning the visible spectrum (that is, <1.7 eV) for solar cell applications. Now, a new perovskite using large propane‐1, 3‐diammonium cation (1, 3‐Pr(NH3 )2 2+ ) with a chemical structure of (1, 3‐Pr(NH3 )2 )0.5 PbI3 is demonstrated. X‐ray diffraction (XRD) shows that the new perovskite exhibits a three‐dimensional tetragonal phase. The band gap of the new perovskite is about 1.6 eV, which is desirable for photovoltaic applications. A (1, 3‐Pr(NH3 )2 )0.5 PbI3 perovskite solar cell (PSC) yields a power conversion efficiency (PCE) of 5.1 %. More importantly, this perovskite is composed of a large hydrophobic cation that provides better moisture resistance compared to CH3 NH3 PbI3 perovskite.